Estimating band diagrams of photonic crystals with multilayer feed-forward neural network - Da Silva Ferreira, Adriano; Malheiros-Silveira, Gilliard Nardel [UNESP]; Hernández-Figueroa, Hugo Enrique (Optica Publishing Group, 2018)
We designed a Multilayer Perceptron (MLP) feed-forward Artificial Neural Network for estimating band diagrams of tri-dimensional photonic crystals. We show a simple and fast-training MLP model able to build accurate band diagrams through speedy computations.